Enhanced in vivo Optical Imaging of the Inflammatory Response to Acute Liver Injury in C57BL/6 Mice Using a Highly Bright Near‐Infrared BODIPY Dye. (9th April 2019) - Sirbu, Dumitru; Luli, Saimir; Leslie, Jack; Oakley, Fiona; Benniston, Andrew C.
Abstract: Delving deeper is possible in whole‐body in vivo imaging using a super‐bright membrane‐targeting BODIPY dye (BD ). The dye was used to monitor homing of ex vivo fluorescently labelled neutrophils to an injured liver of dark‐pigmented C57BL/6 mice. In vivo imaging system (IVIS) data conclusively showed an enhanced signal intensity and a higher signal‐to‐noise ratio in mice receiving neutrophils labelled with theBD dye relative to those labelled with a gold standard dye at 2 h post in vivo administration of fluorescently labelled cells. Fluorescence‐activated cell sorting (FACS) confirmed thatBD is nontoxic, and an exceptional cell labelling dye that opens up precision deep‐organ in vivo imaging of inflammation in mice routinely used for biomedical research. The origin of enhanced performance is identified with the molecular structure and the distinct localisation of the dye within cells that enable remarkable changes in its optical parameters. Abstract : Blinded by the light : A super‐bright membrane‐targeting BODIPY dye opens up deep‐seated organ imaging in full immune system mice. Its enhanced signal‐to‐noise ratio and low cytotoxicity allows performing previously inaccessible fine‐imaging experiments on live specimens. The dye also allows the imaging of fewer cells, an advantage for cell tracking by an in vivo imaging system because of the lower detection limit possible in terms of the numbers of cells that can be identified.